ASPEK MAKRO DAN MIKRO PADA MANTRA PENJAGAAN (KEBUN, BADAN DAN BISA BINATANG) MASYARAKAT MELAYU KEMUJA - Sofiyullah, Muhammad; Missriani, Missriani (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2023)
The problem in this research is what are the macro and micro aspects of the guarding mantra (garden, body and animal venom) of the Kemuja Malay community. The purpose of this study was to find out and describe the macro and micro aspects of the guarding mantra (garden, body, and animal venom) of the Kemuja Malay community. Keywords : Oral Literature, Guard Spells, Macro, Micro.